Synthesis of 2-Hydroxy-3-nitro/amino-5-methyl-a-substituted Thiocarbamidoacetophenones - Aswale, S.R.; Aswale, S.S.; Gawhale, N.D.; Kodape, M.M. (Asian Journal of Chemistry, 2012)
The interactions of 2-hydroxy-3-nitro/amino-5-methyl-a-bromoacetophenone (1) with various thioureas (5a-f) in 1:1 molar proportion in acetone-ethanol medium on water bath for 6 h in round bottom flask to synthesis new series of 2-hydroxy-3-nitro/amino-5-methyl-a-substituted thiocarbamidoacetophenones (6a-f). The synthesized compounds in these reaction conditions have been characterized on the basis of conventional elemental analysis, chemical characteristic and IR, NMR spectral data.